2019
DOI: 10.1371/journal.ppat.1007920
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences between native HIV-1 envelope glycoprotein trimers and stabilized soluble trimer mimetics

Abstract: The HIV-1 envelope glycoprotein (Env) trimer is located on the surface of the virus and is the target of broadly neutralizing antibodies (bNAbs). Recombinant native-like soluble Env trimer mimetics, such as SOSIP trimers, have taken a central role in HIV-1 vaccine research aimed at inducing bNAbs. We therefore performed a direct and thorough comparison of a full-length unmodified Env trimer containing the transmembrane domain and the cytoplasmic tail, with the sequence matched soluble SOSIP trimer, both based … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 61 publications
1
61
0
Order By: Relevance
“…Due to the complexities of the triggering mechanisms for other type I systems, comparatively less is known about how they function. Perhaps the next best characterized system after HA is HIV-1 Envelope (Env) fusion glycoprotein, which is activated by two successive receptor binding events [4,75,[88][89][90][91][92]. Env first binds the CD4 receptor on the surface of T-cells which induces reorganization of the gp120 receptor binding domain and exposure of the co-receptor binding site enabling binding of either CCR5 or CXCR4 [7,92].…”
Section: Despite Their Common Architectures Activation Mechanisms Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complexities of the triggering mechanisms for other type I systems, comparatively less is known about how they function. Perhaps the next best characterized system after HA is HIV-1 Envelope (Env) fusion glycoprotein, which is activated by two successive receptor binding events [4,75,[88][89][90][91][92]. Env first binds the CD4 receptor on the surface of T-cells which induces reorganization of the gp120 receptor binding domain and exposure of the co-receptor binding site enabling binding of either CCR5 or CXCR4 [7,92].…”
Section: Despite Their Common Architectures Activation Mechanisms Anmentioning
confidence: 99%
“…Env first binds the CD4 receptor on the surface of T-cells which induces reorganization of the gp120 receptor binding domain and exposure of the co-receptor binding site enabling binding of either CCR5 or CXCR4 [7,92]. Recently cryo-EM, sm-FRET, and HDX-MS have been used to characterize the structure of Env in the apo and CD4-bound conformations, illuminating how CD4 binding induces long-range conformational changes throughout Env, priming it for coreceptor binding [75,[88][89][90][91]. Sm-FRET revealed that even receptor-naive Env dynamically samples multiple conformations at equilibrium, including a state that seems to mimic the CD4-bound state [75,[89][90][91].…”
Section: Despite Their Common Architectures Activation Mechanisms Anmentioning
confidence: 99%
“…We have compared our structure with those for complexes of a cleaved, B-clade gp160 with Fabs from antibodies PGT145, which binds at the trimer apex (one Fab per trimer, somewhat like PG16, but with an even longer HCDR3)(PDB ID: 6NIJ) [37], and PGT151, which binds over the fusion peptide of gp41 (but only two sites per trimer occupied)(PDB ID: 5FUU) [38]. The structures of gp120-gp41 "protomers" from all three superpose very closely, despite the sequence differences that accompany clade divergence (Fig.…”
Section: Comparison With Two Other Fab-gp160 Complexesmentioning
confidence: 99%
“…45 Indeed, the structure of a PGT151-bound full length Env trimer that was purified by detergent solubilization of cell surface expressed gp160 demonstrated contacts between the topological layers of gp120 and the gp41 three-helix bundle consistent with the conclusion that the mutations were targeting an allosteric network common to both the native Env and engineered SOSIPs. 46 Recent structures of the full length, detergent-solubilized gp160 SOSIP trimers in complex with PGT145 or PG16 showed a similar overall structure of the SOSIP Env, and also showed similar gp120 topological layer contacts with the gp41 3-helix bundle 47,48 , lending further support for the generality of these contacts and the proposed mechanism of Env allostery. Based on these results, we propose a sequential mechanism by which the HIV-1 Env transitions from the prefusion closed state to a fully open, fusion-competent state through a series of sequential steps (figure 7D).…”
Section: Discussionmentioning
confidence: 67%
“…Centroids for the vectors in the analysis included a K46-K490 Cα centroid, W571 and W596 c-αs, c-αs of gp120 excluding variable loops the V1/V1 region residues, and the N- and C-termni, and a V1/V2+V3 c-α centroid Vectors between these reference positions were generated and included a projection of the W596 to K46-K490 centroid vector on to the W596 to W571 vector. Angles, distances, and dihedrals between these vectors were then compiled for a set of available crystal and cryo-EM structures with PDB IDs 4TVP 71 , 4ZMJ 25 , 5ACO 72 , 5CEZ 37 , 5CJX 73 , 5D9Q 74 , 5FYJ 75 , 5FYK 75 , 5FYL 75 , 5T3X 76 , 5T3Z 76 , 5U7M 33 , 5U7O 33 , 5UTF 13 , 5V7J 77 , 5V8L 78 , 5V8M 78 , 6CDE 38 , 6CDI 38 , 6CH7 79 , 6CH8 79 , 6CUE 80 , 6CUF 81 , and 6DE7 12 , 5THR 26 , 5VN3 27 , 5VN8 73 , 6CM3 31 , 6EDU 31 , 5FUU 82 , 6DCQ 46 , 6MAR 83 , 5U1F 55 , 5C7K 84 , 5I8H 85 , 5UM8 86 , 5UTY 13 , 5VIY 87 , 5VJ6 87 , 5WDU 14 , 6B0N 88 , 6CCB 89 , 6CE0 11 , 6CH9 79 , 6CHB 79 , 6CK9 90 , 6DCQ 46 , 6DID 91 , 6E5P 92 , 6IEQ 93 , 6MCO 94 , 6MDT 94 , 6MN7 95 , 6MPG 96 , 6MPH 96 , 6MTJ 97 , 6MTN 97 , 6MU6 97 , 6MU7 97 , 6MU8 97 , 6MUF 97 , 6MUG 97 , 6N1V 96 , 6N1W 96 , 6NC2 98 , 6NC3 98 , 6NF2 96 , 6NIJ 47 , 6NM6 99 , 6NNF 99 , 6NNJ 99 , 6OHY 100 , 6OKP 101 , 6OLP 47 , 6ORN 39 , 6ORO 39 , 6OR...…”
Section: Methodsmentioning
confidence: 99%